Molecular Weight Measurements of Low Molecular Weight Heparins by Gel Permeation Chromatography - Mulloy, B; Gee, C; Wheeler, S F; Wait, R; Gray, E; Barrowcliffe, T W (Thrombosis and Haemostasis, 1997)
The molecular weight profiles of low molecular weight heparin samples have been measured by high-performance gel permeation chromatography using as calibrant the heparinase-degraded material (90/686) now established as the 1st International Reference Preparation (IRP) Low Molecular Weight Heparin for Molecular Weight Calibration. Use of the calibrant as a broad molecular weight standard is described and a calibration table provided based on data collected over several years in one laboratory.In order to confirm the assignment of degree of polymerisation to resolved oligosaccharide peaks in the calibrant, molecular weights of oligosaccharides fractionated from the 1st IRP were independently determined by fast atom bombardment mass spectrometry (FAB MS).The molecular weight distributions of commercial low molecular weight heparins have been characterized. Measurements of molecular weight parameters of heparin molecular weight standards from several sources provide comparisons between the molecular weight scales of this and other studies.